Rencana pemberian ASI dan pemilihan alat kontrasepsi pada ibu hamil di Yogyakarta - Nanik Setiyawati; Niken Meilani (Poltekkes Kemenkes Yogyakarta, 2016)
Antenatal care is focused on interventions to help reduce morbidity and mortality of mothers and newborns. One of the goals of integrated antenatal care is to provide antenatal services integrated, comprehensive and quality, including family planning counseling and breastfeeding. Formula feeding in infants in DIY is 87%, above Indonesia amounted to 79.8%. The studyaims to determine the plan of exclusive breastfeeding and contraceptive choice in pregnant women in Yogyakarta. This research is a quantitative analytic correlational cross-sectional method. Data is collected in health centers in DIY from August until October 2014. The population was all pregnant women who visit in health center of Mantrijeron, Sleman, Sewon II, Karangmojo I and Galur I. Samples were using cluster sampling as 94 respondents. The results showed that 84% of respondents intend to give the baby breast milk until the age of 12 months and 18% of mothers planning to breastfeed for less than 6 months. Majority of mother's age <29 years and> 29 years plans to breastfeedding. A lot of primigravida plan breastfeeding than multigravida. Mothers with secondary education more intent breastfeeding, mothers who do not work while more are planning to breastfeed. 54.3% of respondents chose injectables. Respondents were <29 years 68.6% chose injections, age> 29 years chose sterile 14%. Primigravidas choose injectables 61.5%, 37.5% chose KB multigravida sterile. Respondents with basic education, secondary and higher majority chose injectables. Respondents who worked and did not work the majority chose injectables.